Pengaruh Locus Of Control dan Need For Achievement Terhadap Intensi Berwirausaha Pada Siswa MAN 1 Kota Payakumbuh - Cindy Fatika; Rose Rahmidani (Universitas Negeri Padang, 2022)
The goal of this study is to determine the effect of locus of control and the need for achievement on the entrepreneurial intentions of MAN 1 Payakumbuh students. The causative form was used in this study, and the population consisted of MAN 1 Payakumbuh students. The survey sample consists of 260 respondents who were chosen using a proportional random sampling technique. This study relied on primary data gathered through the distribution of questionnaires to selected MAN 1 Payakumbuh students. SPSS 20 path analysis was used as the analysis method. The findings of this study indicate that the locus of control and the need for achievement have a significant impact on entrepreneurial intentions. The locus of control influences entrepreneurial intentions significantly. The need for achievement has a significant impact on entrepreneurial intentions.